Propagation of short current pulses in Josephson transition line and ultrafast qubit control. (December 2019) - Bastrakova, M V; Klenov, N V; Ruzhickiy, V I; Satanin, A M
Abstract: The results of the study of the impact of single-quantum magnetic flux pulses moving along the Josephson transmission lines (JTL) on the dynamics of states of qubits magnetically coupled with such lines are presented. The JTL dynamics was calculated in the frame of resistively shunted junction model with different damping coefficients. This allowed us to find the form of control current pulses (fluxon) acting on a superconducting qubit. Numerical simulations of the simplest logic operations with superconducting qubit due to calculated fluxon impact are presented.